2013
DOI: 10.1163/15685411-00002715
|View full text |Cite
|
Sign up to set email alerts
|

Integrated approach for the management of the root-knot nematode, Meloidogyne incognita, on eggplant under field conditions

Abstract: A 2-year field study was conducted to develop an eco-friendly field application method for controlling root-knot disease of eggplant {Solanum melongena). The test sites were heavily infested with the root-knot nematode, Meloidogyne incognita. The efficacy of neem cake (1.5 t ha~'), talc-based preparations of Pseudomonas fluorescens (10 kg ha~') and Trichoderma harzianum (10 kg ha~') as soil application and seed treatment (10 g (kg seed)"') were tested to develop an integrated nematode management module against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…Both practices are important component of present IPM technology which are used as pre-treatment to reduce initial inoculum level of rice rootknot nematode, M. graminicola. Our observations confirmed previous reports that fallowing and summer ploughing when applied as pre-treatment, reduced M. incognita population by up to 51% and 53.8% on eggplant (Singh 2013) and on chilli crop (Singh and Singh 2012) respectively.…”
Section: Resultssupporting
confidence: 92%
“…Both practices are important component of present IPM technology which are used as pre-treatment to reduce initial inoculum level of rice rootknot nematode, M. graminicola. Our observations confirmed previous reports that fallowing and summer ploughing when applied as pre-treatment, reduced M. incognita population by up to 51% and 53.8% on eggplant (Singh 2013) and on chilli crop (Singh and Singh 2012) respectively.…”
Section: Resultssupporting
confidence: 92%
“…Commercial products of P. flourescens and T. harzianum are available in the market which may be more adaptive and less expensive. Increase in the efficacy of these bio-agents appears possible when these bio-agents are integrated with organic amendments such as oil cakes (Verma et al 2005, Singh 2013) and this has been demonstrated in the present investigation. It is also recorded in the present study that neem cake enhanced plant growth and yield during consequent second season's trial.…”
Section: Pretreatmentsupporting
confidence: 61%
“…In India, the efficacy of current strategies for management of root-knot disease is limited and bitter gourd production is achieved through chemical pesticides. In developing countries like India, integrated nematode management is required, as profit margins and environmental consideration preclude the use of chemical control (Singh 2013).…”
mentioning
confidence: 99%
“…Among all the tested bio-agents, bio-agents liquid formuations ( T. viride + P. fluorescence + P. lilacinum ) significantly improved the plant growth and reduced disease severity might be due to the combined effects of all bio-agents. Several researchers proved that combined application of bio-agents has been effective in management of M. incognita and F. oxysporum either inoculated individually or simultaneously in various vegetable crops under in vivo or field (protected/open) conditions ( Singh et al, 2020 , Abo-Elyousr et al, 2014 , Singh et al, 2013 , Singh, 2013 , Singh, 2019 , Singh and Singh, 2012 , Dubey et al, 2007 ). In present study, combined application of egg parasitic fungus, P. lilacinum , antagonistic fungus, T. viride and bacterial antagonists P. fluorescens was shown increased efficiency in cucumber plants under protected conditions may be the reason that the bio-agents colonisation was more due to favourable conditions (micro climate) maintained in protected structures.…”
Section: Discussionmentioning
confidence: 99%